2021
DOI: 10.3390/e24010058
|View full text |Cite
|
Sign up to set email alerts
|

Many-Objective Quantum-Inspired Particle Swarm Optimization Algorithm for Placement of Virtual Machines in Smart Computing Cloud

Abstract: Particle swarm optimization algorithm (PSO) is an effective metaheuristic that can determine Pareto-optimal solutions. We propose an extended PSO by introducing quantum gates in order to ensure the diversity of particle populations that are looking for efficient alternatives. The quality of solutions was verified in the issue of assignment of resources in the computing cloud to improve the live migration of virtual machines. We consider the multi-criteria optimization problem of deep learning-based models embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The IQHPSO algorithm starts by initializing the swarm with random positions and velocities. The positions and velocities are then updated iteratively using the QRG operator and the adaptive parameter tuning technique [26]. The global best particle is updated using the global best selection strategy.…”
Section: Detailed Explanation Of the Improved Quantum-inspired Hybrid...mentioning
confidence: 99%
“…The IQHPSO algorithm starts by initializing the swarm with random positions and velocities. The positions and velocities are then updated iteratively using the QRG operator and the adaptive parameter tuning technique [26]. The global best particle is updated using the global best selection strategy.…”
Section: Detailed Explanation Of the Improved Quantum-inspired Hybrid...mentioning
confidence: 99%
“…The multi-objective optimization problem usually focuses on two/three objectives where the values of the objectives that create the best trade-off are considered optimal solutions. A special type of multi-objective problem, with the optimization of four or more objectives, is usually presented as a many-objective problem [12], [14], [25], [30].…”
Section: Figure 2 the General Framework Of Multi-direction Qosmentioning
confidence: 99%
“…It requires higher allocated memory to the archived solutions. So the number of Pareto front solutions and their order in the memory will be important in the evolutionary algorithms [14], [34].…”
Section: Figure 2 the General Framework Of Multi-direction Qosmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [32] proposes a quantum behavior particle swarm optimization algorithm with a dynamic learning strategy, aiming to improve the performance and adaptability of the algorithm. Jerzy Balicki conducted a many-objective quantum-inspired particle swarm optimization algorithm and confirmed that multi-objective quantum-inspired particle swarm optimization algorithms provide better solutions than other metaheuristics [33]. Arnaud Flori proposed a quantum particle swarm optimization (QUAPSO), which simplifies the setup of the algorithm by setting the velocity PSO parameter on top of the quantum superposition [34].…”
Section: Introductionmentioning
confidence: 99%